Norleual, a hepatocyte growth factor and macrophage stimulating protein dual antagonist, increases pancreatic cancer sensitivity to gemcitabine. Issue 4 (April 2018) - Church, Kevin J.; Vanderwerff, Brett R.; Riggers, Rachelle R.; Mateo-Victoriano, Beatriz; Fagnan, Matthew; Harris, Phillip H.; LeValley, Jewel C.; Harding, Joseph W.
Abstract : Pancreatic cancer is a leading cause of cancer deaths in the USA and is characterized by an exceptionally poor long-term survival rate compared with other major cancers. The hepatocyte growth factor (HGF) and macrophage stimulating protein (MSP) growth factor systems are frequently over-activated in pancreatic cancer and significantly contribute to cancer progression, metastasis, and chemotherapeutic resistance. Small molecules homologous to the 'hinge' region of HGF, which participates in its dimerization and activation, had been developed and shown to bind HGF with high affinity, antagonize HGF's actions, and possess anticancer activity. Encouraged by sequence homology between HGF's hinge region and a similar sequence in MSP, our laboratory previously investigated and determined that these same antagonists could also block MSP-dependent cellular responses. Thus, the purpose of this study was to establish that the dual HGF/MSP antagonist Norleual could inhibit the prosurvival activity imparted by both HGF and MSP to pancreatic cancer cells in vitro, and to determine whether this effect translated into an improved chemotherapeutic impact for gemcitabine when delivered in combination in a human pancreatic cancer xenograft model. Our results demonstrate that Norleual does indeed suppress HGF's and MSP's prosurvival effects as well as sensitizing pancreatic cancer cells to gemcitabine in vitro . Most importantly, treatment with Norleual in combination with gemcitabine markedly inhibited in-vivo tumor growth beyond the suppression observed with gemcitabine alone. These results suggest that dual functional HGF/MSP antagonists like Norleual warrant further development and may offer an improved therapeutic outcome for pancreatic cancer patients.